Clinical significance of plasma fibrinogen level as a predictive marker for postoperative recurrence of esophageal squamous cell carcinoma in patients receiving neoadjuvant treatment. Issue 7 (27th August 2013) - Matsuda, S.; Takeuchi, H.; Fukuda, K.; Nakamura, R.; Takahashi, T.; Wada, N.; Kawakubo, H.; Saikawa, Y.; Omori, T.; Kitagawa, Y.
Summary Among multidisciplinary therapies developed for advanced esophageal cancer, neoadjuvant chemotherapy and chemoradiotherapy have been established as standard treatments. To deliver cautious follow up and intense treatment for high‐risk patients, a simple and instructive biomarker for the postoperative recurrence needs to be identified. Fibrinogen, a common component of hemostasis, has been suggested to not only play an important role in cancer metastasis, but also correlate with tumor recurrence. We aim to clarify the validity of plasma fibrinogen as a marker for predicting the postoperative recurrence of esophageal squamous cell carcinoma patients who received neoadjuvant treatment. We reviewed 72 consecutive patients with esophageal squamous cell carcinoma who received neoadjuvant chemotherapy or chemoradiotherapy, followed by esophagectomy at the Keio University Hospital from 2001 to 2010. Of them, we retrospectively examined 68 patients who underwent plasma fibrinogen examination before and after neoadjuvant treatment and underwent transthoracic radical esophagectomy. We investigated patient characteristics, clinicopathological factors, neoadjuvant treatment effects, postoperative course, and plasma fibrinogen levels. We investigated pretreatment and preoperative (postneoadjuvant treatment) plasma fibrinogen levels, as well as changes in fibrinogen levels before and after neoadjuvant treatment. Patients with preoperative hyperfibrinogenemia (>350 mg/dL) and patients with increased plasma fibrinogen levels during neoadjuvant treatment showed significantly shorter postoperative disease‐free survival (DFS) (P = 0.002 and P = 0.037, respectively). Moreover, we classified these patients into three classes on the basis of their preoperative fibrinogen levels and changes in fibrinogen levels during neoadjuvant treatment. Patients who had both high preoperative plasma fibrinogen and increased fibrinogen levels showed significantly shorter DFS than others. In contrast, patients who had normal preoperative plasma fibrinogen and decreased fibrinogen levels showed significantly longer DFS. Based on this fibrinogen classification, we could differentiate between significantly favorable and poor prognosis patients group. Overall, this classification (hazard ratio = 1.812, P = 0.013) and the response to neoadjuvant treatment (hazard ratio = 0.350, P = 0.007) were found to be significant determining factors for postoperative DFS. With the validity of preoperative plasma fibrinogen levels and changes in fibrinogen levels during neoadjuvant treatment, the plasma fibrinogen level was found to be a possible biomarker for postoperative recurrence in advanced esophageal cancer patients who received neoadjuvant treatment. Moreover, plasma fibrinogen classification could be a simple and valuable predictive marker for postoperative follow up.